Інформаційна модель ЕКГ-дослідження - Філатова, Ганна Євгенівна; Фахс, М. (Видавничий центр "ХАІ", 2019)
The paper presents the development of an ECG-study information model using data flow diagrams. The information model is presented in the form of a context diagram, its decomposition and decomposition of the subsystems “Registration and analysis of biomedical signals with locally concentrated features” and “Diagnostics”. Considering the proposed information model, UML diagrams of the cardiological DSS based on the morphological analysis of biomedical signals and the module for the morphological analysis of the electrocardiogram are developed.
Keywords: серцево-судинна система; медичних інформаційних систем; кардіологічна СППР; програмний код